Postira in the Whirlwind of the 20th Century Aggression - Jelaska, Zrinka (Array, 2009)
This book consists of six parts. Following the introduction the first part of the book is solely dedicated to people who were born or lived in the society of Postira and died as victims during XXth century. The second and the third part consist of scholarly papers (which are peer reviewed). The forth part consists of personal memories and reflexions on last centuries events, as well as six poems. The book ends with one text and several poems, English and Spanish summaries and alphabetical list of 95 victims.